Carta arbitral e a harmonização entre o juízo estatal e arbitral - Della Santa, Felipe Pedroso (2021)
The main objective of this article is an analysis of the institute of arbitration letter, given that the New Code of Civil Procedure brought significant changes, among them the positivization of arbitration as a means of jurisdiction, the harmonization between the two jurisdictions is brought about by the use of arbitration letter, given that from the premise, the arbitration letter mechanism is duly used to receive state judges and the resources that make up the arbitral judges. The arbitration letter consists of a decision of the arbitral court, qualifying the state court to proceed with the practice of a certain act that the arbitral judges do not have jurisdiction or coercive force to practice, it is very common to determine measures that involve the practice of indispensable acts for the production of evidence evidence, to extract specific information from institutions or public bodies through the forwarding of official letters, as well as arbitration executions, taking into account that the arbitral tribunal often does not have full knowledge of documents or does not have sufficient information for the clarification of any controversial fact alleged in the scope of the arbitration procedure, given that the state judges must assist the arbitration judges with regard to measures that can only be carried out by the Judiciary.